Diagnosis of aphasia in stroke populations: A systematic review of language tests. - Alexia Rohde; Linda Worrall; Erin Godecke; Robyn O'Halloran; Anna Farrell; Margaret Massey (PLoS ONE)
Background and purpose Accurate aphasia diagnosis is important in stroke care. A wide range of language tests are available and include informal assessments, tests developed by healthcare institutions and commercially published tests available for purchase in pre-packaged kits. The psychometrics of these tests are often reported online or within the purchased test manuals, not the peer-reviewed literature, therefore the diagnostic capabilities of these measures have not been systematically evaluated. This review aimed to identify both commercial and non-commercial language tests and tests used in stroke care and to examine the diagnostic capabilities of all identified measures in diagnosing aphasia in stroke populations. Methods Language tests were identified through a systematic search of 161 publisher databases, professional and resource websites and language tests reported to be used in stroke care. Two independent reviewers evaluated test manuals or associated resources for cohort or cross-sectional studies reporting the tests' diagnostic capabilities (sensitivity, specificity, likelihood ratios or diagnostic odds ratios) in differentiating aphasic and non-aphasic stroke populations. Results Fifty-six tests met the study eligibility criteria. Six "non-specialist" brief screening tests reported sensitivity and specificity information, however none of these measures reported to meet the specific diagnostic needs of speech pathologists. The 50 remaining measures either did not report validity data (n = 7); did not compare patient test performance with a comparison group (n = 17); included non-stroke participants within their samples (n = 23) or did not compare stroke patient performance against a language reference standard (n = 3). Diagnostic sensitivity analysis was completed for six speech pathology measures (WAB, PICA, CADL-2, ASHA-FACS, Adult FAVRES and EFA-4), however all studies compared aphasic performance with that of non-stroke healthy controls and were consequently excluded from the review. Conclusions No speech pathology test was found which reported diagnostic data for identifying aphasia in stroke populations. A diagnostically validated post-stroke aphasia test is needed.